Penelitian Pemetaan Potensi Hasil Pertanian Di Desa Cupak Kabupaten Jombang - Angga Dutahatmaja; Irma Retno Dewi; Avilla Anggun Arisendy (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Agriculture can be introduced to the community through outreach involving the use of questionnaires, training, and assistance in making food from agricultural products. In this activity, Matching Fund Real Work Lecture students have developed tools and equipment used to support socialization events for making food from agricultural products so that they can be used for a long time and provide benefits to the community. Apart from that, the Matching Fund Real Work Lecture students also created publication articles and activity videos to introduce profiles and methods for making food from agricultural products. There is a socialization stage, the community is given an understanding of the importance of innovation to increase the selling value of agricultural products. For example, teaching about Porang plants, which are not only sold raw, but can also be processed into flour and made into village food. Furthermore, the mentoring stage is carried out to ensure that participants understand their duties and responsibilities and maintain good coordination during the event. The results of the dissemination of Training and Making Village Typical Products with Agricultural Product Diversification have shown a positive impact. Students of the Matching Fund Real Work College and the people of Cupak Village have succeeded in producing processed products such as cookies, kastengel, cendol and cireng.